Internet Use, Reading Habit and Reading Ability of Students of Private Junior High Schools in Kecamatan Ilir Timur II Palembang - Sigit Priambodo; Bambang A. Loeneto; Chuzaimah D. Diem (Script Journal: Journal of Linguistics and English Teaching, 2019)
This study was aimed to find out whether or not (1) there is  any significant correlation between reading ability and reading habit, (2) There is any significant correlation between reading ability and internet use, (3) There is any significant correlation among reading ability, internet use, and reading habit of students of private junior high schools in  Kecamatan Ilir Timur II Palembang. This study was a quantitative research approach with a corelational research design. The researcher collected the data through 2 instruments namely, reading test and questionnaires. A test was used to find out students’ reading ability and questionnaires were used to find out students’ reading habits and internet use. The population of this study was 803 and 120 for the population. To analyze the data, the procedures were presenting and describing the data,  testing the hypotheses, and analyzing the regression. From the results, only internet use and reading ability that had a significant correlation (p-value > 0.05). The result of the regression analysis between internet use to reading ability showed that the correlation between those variables was 16,7%.